Non-thermal melting of tungsten under intense electronic excitations. (1st September 2021) - Ye, X.B.; He, Z.H.; Gao, Fei; Pan, B.C.
Abstract: Non-thermal effect caused by ultrafast lasers and swift ions in materials are very intriguing, which is of both scientific interest and technological importance. However, the underlying physics of non-thermal effect on ultrafast process remains unclear and the proposed mechanisms have been controversial. Based on the perturbation approximation under tight-binding theory, the non-thermal effect on tungsten (W) are extensively studied. We demonstrate that the non-thermal effect stemmed from the intense electronic excitations induce dramatic decrease in the melting point of W crystal, as well as non-thermal melting inside the W slab. Our analysis shows that the non-thermal forces are essentially responsible for the drop of melting point of the bulk system. Remarkably, the non-thermal effect combined with surface effect on a W film enhance the ordering of the direction of atomic motion near the surface, preventing melting near the surface area, but leading to non-thermal melting in the interior area of the film. Our work also exhibits a unified relationship between the non-thermal melting and the interatomic forces. This relationship is universal in metals and semiconductors irradiated by ultrafast lasers or swift ions, and has been well established long before. Graphical abstract: Snapshots of the velocity along z direction ( vz ) of each atom in W (001) slab during the molecular dynamics simulations. Atoms are colored according to the magnitude and direction of ( vz ). Image, graphical abstract